Development of the Learning Activity Package to Enhance Attributes of Scientific Innovator for Upper High School Students - Buxton, Nipaporn; Keeratichamroen, Wasana; Phonnong, Isara (Ratchaphruek Journal, 2025)
This research aimed to synthesize the attributes of scientific innovator and develop the learning activities package to enhance scientific innovator attributes. The study was conducted in two phases: 1) To synthesize the attributes of scientific innovator by reviewing literature on the nature of science, the traits of scientists and innovators, and relevant conceptual frameworks. The evaluation tool used was a suitability assessment form, reviewed by three experts; and 2) Developed a set of learning activities by using mean scores and standard deviation with evaluations conducted by five experts. The assessment tool employed was a checklist for evaluating the components of the learning activities. The findings revealed five key attributes of scientific innovator: (1) Scientific challenge; (2) Scientific initiative and connectivity; (3) Scientific prediction; (4) Scientific communication; and (5) Entrepreneur. The index of item-objective congruence (IOC) for all attributes was 1.00, indicating high suitability and applicability. The developed learning activity package consisted of four components: (1) learning objective, (2) instructions and introduction, (3) learning activities, and (4) assessment and evaluation. Among these, learning objectives received the highest mean score ( = 4.60, S.D. = 0.52), while assessment and evaluation had the lowest mean score at a high level ( = 4.16, S.D. = 0.50). Overall, the package was rated at a high level of appropriateness ( = 4.44, S.D. = 0.51), confirming its suitability for enhancing the attributes of scientific innovator for students.